"Three‐in‐One" Strategy that Ensures V2O5·nH2O with Superior Zn2+ Storage by Simultaneous Protonated Polyaniline Intercalation and Encapsulation. Issue 4 (10th March 2022) - Sun, Jingjing; Zhao, Yunfeng; Liu, Yanyan; Jiang, Hanmei; Huang, Chi; Cui, Miao; Hu, Tao; Meng, Changgong; Zhang, Yifu
Abstract : The structural engineering of vanadium oxides is considered as a research hotspot for enhancing their electrochemical performances applied to aqueous zinc‐ion batteries (AZIBs). In regard to the laggard Zn 2+ transfer kinetic and fragile structure of V2 O5 · n H2 O, herein, a feasible "three‐in‐one" strategy is adopted to design the structural engineering of V2 O5 · n H2 O nanobelts through simultaneous protonated polyaniline intercalation and encapsulation (denoted as P‐VOH@P) to boost their Zn 2+ storage. First, the enlarged interlayer pillared by polyaniline accelerates Zn 2+ transfer speed and weakens electrostatic attraction between negative [VO] units and positive Zn 2+ . Second, polyaniline shell directly stabilizes the P‐VOH@P heterostructure. Third, the composition of protonated polyaniline not only improves the conductivity, but also contributes partial capacity though the reversible intrachain electronic migration. As expected, the Zn//P‐VOH@P cell exhibits specific capacities of 387 mAh g −1 with low‐mass‐loading cathode (2 mg cm −2 ) and 345 mAh g −1 with high‐mass‐loading cathode (5 mg cm −2 ) in coin cells and 360 mAh g −1 in pouch cells at 0.1 A g −1 . Furthermore, the Zn//P‐VOH@P cell shows low capacity decay and good rate property. Herein, light is shed on a new strategy of engineering the vanadium oxide structure for postgeneration cathode material and paves a novel way to the advanced energy‐storage system. Abstract : A "three‐in‐one" strategy is adopted to design simultaneous intercalation and encapsulation of protonated polyaniline for V2 O5 · n H2 O nanobelts. The enlarged interlayer and protonated polyaniline endow the Zn//P‐VOH@P cell with high capacity. The polyaniline shell and weakened electrostatic attraction improve the stability. Herein, a new path for structural engineering is offered and the intrachain electronic migration mechanism of polyaniline is proposed.